Fire resistance for square tubular joints with and without chord reinforcement - Yang, J. (2013)
The chord surface around the brace/chord weld toe for a square welded tubular joint is the critical position because failure occurs frequently at this location due to the weak stiffness in the transverse direction of the chord which is generally a thin-walled tube. To improve the load carrying capacity, the chord of a square tubular joint can be strengthened locally near the joint connection. Through Finite Element (FE) analysis, the fire resistance of both un-reinforced and chord reinforced tubular T-joints is investigated. The chord reinforcing measure for the T-joints is increasing the chord thickness around the brace/chord intersection locally. In the FE analysis, the duration of fire resistance, the reaction force in restrained chord ends and the deforming process of two typical tubular T-joints under axial compression are analyzed and discussed. The effect of brace axial loading ratio on the fire resistance is also considered. Based on the FE analysis, it is found that a tubular joint with chord reinforcement has a much longer duration of fire resistance compared to an un-reinforced joint. In addition, the failure mode of a chord reinforced tubular joint model can be changed to tube yielding if a suitable reinforcing scheme is used while joint failure is always the dominant mode for an un-reinforced tubular joint.